Comparison of two conservative methods in treatment of ureteric stones - Ravikoti Reddy Konatham; Rajendra Prasad K; Harshitha K (International Journal of Health and Clinical Research, 2022)
Background: Urolithiasis is important major public health problem. This study was undertaken in order to compare the efficacy of tamsulosin in comparison with the oral fluids. Material and Methods: A comparative study was undertaken among 50 patients where the patients were equally divided in to two equal groups of 25 patients each. One group received oral fluids and other group received tamsulosin. The patients were observed strictly on weekly basis and asked for any history of passage of calculi and findings were recorded and patients were monitored and followed up for a period of one month. Results: Majority of the patients in Oral fluids and Tamsulosin group were males and aged between 41 – 50 years. Right ureter was affected in majority of the patients. Lower 1/3rd of the Ureter is affected among 36% of the oral fluid group and 40% of the Tamsulosin group. About 56% of the oral fluid group patients had stone size of less than 5 mm and 56% of the patients in Tamsulosin group had stone size of 6 – 10 mm. About 32% of the patients in oral fluid group passed the stone by 21 days of follow up and 48% of the patients in Tamsulosin group passed the stone by 14 days of follow up. Giddiness was noted in 16% and Headache was noted in 8% of the patients in Tamsulosin group. No side effects were noted in Oral fluids group. Conclusion: The tamsulosin group had expulsion of ureteric stones when compared to the oral fluid group.